VULNERABILITY OF WOMEN IN NATURAL CALAMITIES IN KENYA: THE BUNYALA FLOODS EXPERIENCES - Huho, Julius M. (Advances in Social Sciences Research Journal, 2015)
Floods, like any other disasters, cause a great deal of human suffering especially to the vulnerable members of the society. In Kenya floods are perennial and affect thousands of people. The worst affected areas are the low lands of the five major drainage basins. Bunyala sub-county which lies in the Lake Victoria basin, experiences perennial floods due to overtopping of Rivers Nzoia and Yala at their lower reaches near Lake Victoria. These floods are accompanied by massive destruction of socio-cultural and economic activities of the inhabitants. The most vulnerable and the most affected are women since they do not only carry the burden of fending for their families but also take care of the affected relatives. This study examined the social impacts of floods on women in Bunyala sub-county.